Text difficulty vs text readability: Students’ voices - Agus Widyantoro; Jamilah Jamilah; Ari Purnawan (EduLite: Journal of English Education, Literature and Culture, 2022)
Reading is an essential skill to be mastered, especially by university students and it is the lecturers’ responsibility to train their students to develop their reading skill. In order to do so, lecturers will have to develop materials or choose materials from existing books to be used in the teaching learning process. The text difficulty must be appropriate to the students’ English proficiency level. This study was aimed at finding the students’ perceptions of the difficulty of the texts used in the reading class and the corresponding text readability. This study utilized the survey design and the content analysis involving 141 second semester students of the English Language Education Department of a state university. Questionnaires were used to get data on students’ perceptions of the text difficulty and the text readability was analysed with the help of https://readabilityformulas.com. The data on students’ perceptions were analysed using percentage while the data on the text readability were analysed using the readability test. The findings showed that there was a difference in the students’ perception of the difficulty of the text and the readability level as being calculated using different readability formulas.